„You Can Run but You Can’t Hide “– The Role of Avoidant Coping in Mental Health of Athletes during COVID-19 Pandemic: English - Barzut, Vesna; Đurović, Dušanka; Novakov, Ivana (Primenjena psihologija, 2023)
This study aimed to investigate the psychological functioning of athletes in Serbia during the second wave of the COVID-19 pandemic. We investigated the relationships of different coping strategies (problem-focused, emotion-focused, and avoidant coping), intolerance of uncertainty, and perceived levels of depression, anxiety, and stress. A total of 117 athletes took part in this study (62.40% male, average age 29.95). The results showed that the use of avoidant coping and problem-focused strategies were associated with poorer indicators of mental health. Furthermore, intolerance of uncertainty had both direct and indirect (via avoidant coping strategies) effects on experienced levels of depression, anxiety, and stress.